Corruption and Growth: Evidence from the Italian regions - Nadia Fiorino; Emma Galli; Ilaria Petrarca (European Journal of Government and Economics (EJGE), 2012)
This paper investigates the impact of corruption on economic growth in the Italian Regions. We estimate a dynamic growth model for the period 1980-2004 addressing both the potential bias of the measures of corruption and the endogeneity between corruption and economic development. We find strong evidence of a negative correlation between corruption and growth. Moreover, since government intervention has been traditionally used to reduce income differentials between the Northern and the Southern regions, we also analyze the interaction between corruption and government expenditure. Our results indicate that corruption undermines the positive impact that public expenditures have on economic growth.
Keywords: 330; corruption; associative crimes; economic growth; dynamic estimation